Habitus Mempengaruhi Gaya Hidup Dan Identitas Sosial Mahasiswa Universitas Negeri Jakarta Menurut Perspektif Bourdieu (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research examines the influence of habitus on the lifestyle and social identity of Jakarta State University students through Pierre Bourdieu's perspective. Habitus, as a set of internal dispositions resulting from interactions with social structures, plays an important role in shaping individuals' mindsets, values and preferences. This research focuses on how factors such as socio-economic background, family education, friendship experiences, and interactions with peers and lecturers influence the formation of students' habitus. Furthermore, it explores how habitus influences lifestyles, including consumption patterns and cultural preferences, as well as social identities that shape students' self-perceptions within the context of a particular social group. Through a qualitative approach, this study aims to understand the relationship between habitus, lifestyle, and social identity of students, as well as the implications of these findings for the development of educational policies in the campus environment.